Prospective evaluation of the sialoadenectomy as treatment for giant sialolith in the submandibular gland: Case series - Silva, Jonathan Ribeiro da; Bonardi, Joao Paulo; Pereira, Rodrigo dos Santos; Albuquerque, Camila; da-Rocha-Júnior, Hernando Valentim; Hochuli-Vieira, Eduardo (Journal of Oral Diagnosis, 2018)
Objective: The objective of this study is to report a series of cases of giant submandibular gland sialoliths treated by sialoadenectomy. Methods: Nine patients were admitted to the Maxillofacial Surgery Department of Nova Iguaçu General Hospital from 01/01/2012 to 01/05/16, presenting submandibular gland sialoliths larger than 1.5 cm without response to conservative treatment. All patients underwent sialoadenectomy through cervical access. Results: Patients presented a mean age of 51 years, with 7 being male and 2 being female. The size of the sialoliths removed ranged from 1.8 to 4.9 cm. None of the patients presented hypoglossal nerve complications, 2 had transitory marginal mandibular nerve palsy, and 2 patients had postoperative infections in the first week. Conclusion: We can conclude that giant sialoliths represent a greater difficulty for the treatment of sialolithiasis, where sialoadenectomy represents a resolutive therapy with few complications.